Three-dimensional-printed porous prosthesis for the joint-sparing reconstruction of the proximal humeral tumorous defect - Zhang, Yuqi; Lu, Minxun; Hu, Xin; Li, Zhuangzhuang; Wang, Jie; Gong, Taojun; Zhou, Yong; Luo, Li; Min, Li; Tu, Chongqi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Tumorous bone defect reconstructions of the proximal humerus with joint sparing is a challenge. Numerous reconstruction methods have been proposed, but the proximal residual humerus is commonly sacrificed because of the extremely short length. To preserve the proximal humerus and improve clinical outcomes, we designed a 3D-printed uncemented prostheses with a porous structure to treat tumorous bone defects of the proximal humerus. Methods: Our analysis included seven patients treated between March 2018 and July 2019. A 3D model was established, and related data was measured, including the diameter of the humeral head, the resection length, and the residual length. A prosthesis was designed and fabricated based on these data. Functional and oncologic outcomes were recorded, and complications and osseointegration were evaluated. Results: The mean age of the patients was 20.3 years, and median follow-up period was 26 months. The lengths of the residual proximal humerus were 17.9 mm on average. All the patients had preserved humeral heads and most of the rotator cuff was intact. Average postoperative range of movement (ROM) of the affected shoulder was 83.8°; ﬂexion, 82.5°; extension, 43.8°; adduction, 16.3°. Averaged Musculoskeletal Tumor Society score (MSTS) was 94.3%. Good osseointegration was observed on the interface between the bone and prosthesis. Conclusion: A 3D-printed porous prosthesis with cone-like structures successfully achieved joint-sparing reconstruction of proximal humeral tumorous defects with satisfying function outcomes. The preservation of the rotator cuff and humeral head plays an essential role in the function of the shoulder joint.